Assessment of bilateral pupillary centroid characteristics at varying illuminations and post‐photopic flash response using an automated pupillometer. (19th July 2016) - Prakash, Gaurav; Srivastava, Dhruv; Suhail, Muhammad; Bacero, Ruthchel
Abstract : Background: The aim was to assess the symmetry and magnitude of illumination‐dependent centroid shift and of post‐photic flash re‐dilatation response for normal pupils. Methods: This cross‐sectional, observational, inter‐eye comparative study was performed at a specialty hospital. Fifty eyes (25 volunteers) without any ocular abnormality underwent pupillometry for scotopic (0.4 lux), mesopic (4.0 lux), photopic conditions (40 lux) and for rate of pupillary re‐dilatation after a photopic flash (500 lux) with an inbuilt pupillometer on a Scheimpflug device (Sirius, CSO, Italy). Main outcome measures were pupillary centroids at different illuminations and time‐dependent pupil diameters after a photic flash response. Results: The mean pupil size for scotopic, photopic and mesopic pupils were significantly different (p < 0.001, ANOVA) for right and left eyes, analysed separately. The post‐photic flash re‐dilatation diameter was measured at zero, one, two, four, six, eight and 10 seconds after the flash. The mean diameters at given times post‐photic flash were comparable in fellow eyes (p > 0.5, t‐test) and highly correlated (r ≥ 0.8, p < 0.05 at all timed comparisons). The mean pupil diameter followed a time‐dependent cubic function for both the right and left eyes. Speed was also governed by a time‐dependent cubic function for both the right and the left eyes. Conclusions: Fellow eye symmetry is seen in illumination‐governed centroid shifts and the post‐flash re‐dilatation response. The pupil dilates back briskly with a time‐dependent cubic function, which is similar for fellow eyes in normal patients.